2022
DOI: 10.1002/vms3.798
|View full text |Cite
|
Sign up to set email alerts
|

Choline diet improves serum lipid parameters and alters egg composition in breeder ducks

Abstract: Background Choline is an important nutrient, playing key roles in numerous metabolic pathways relevant to animal health. Objectives The objective of this study was to evaluate the effect of dietary choline on the lipid parameters, cardiovascular health (CVH), and levels of egg trimethylamine (TMA) and cholesterol in breeder ducks during the late laying period. Methods A total of 60 Jingjiang ducks were randomly separated into six replicates of 10 ducks each. After peak production until 65 weeks of age, the bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…La colina suplementaria en la dieta tuvo un efecto beneficioso sobre los parámetros lipídicos y la salud cardiovascular de los patos reproductores, ya que aumentó los niveles séricos de HDL-C y disminuyó el índice de ateroesclerosis, un predictor del riesgo de enfermedad cardiovascular en patos. Aunque aumentó los niveles de trimetilamina en la yema de huevo en patos, no alteró la concentración de colesterol en la yema de huevo, evidenciado que la suplementación con colina en la dieta mejora los parámetros de lípidos y salud cardiovascular en patos (Song et al, 2022).…”
Section: Colinaunclassified
“…La colina suplementaria en la dieta tuvo un efecto beneficioso sobre los parámetros lipídicos y la salud cardiovascular de los patos reproductores, ya que aumentó los niveles séricos de HDL-C y disminuyó el índice de ateroesclerosis, un predictor del riesgo de enfermedad cardiovascular en patos. Aunque aumentó los niveles de trimetilamina en la yema de huevo en patos, no alteró la concentración de colesterol en la yema de huevo, evidenciado que la suplementación con colina en la dieta mejora los parámetros de lípidos y salud cardiovascular en patos (Song et al, 2022).…”
Section: Colinaunclassified
“…Population-level assessments of dietary consumption of choline showed that choline intake varies approximately 4 times or higher. , Numerous studies have shown that high-choline diets (HCD) caused an increase in oxidative stress and inflammation levels as well as promoted dyslipidemia and lipid accumulation, and increased the risk of atherosclerotic cardiovascular disease (CVD). Moreover, previous studies had found that thyroid lesions had notably elevated choline levels than healthy adjacent thyroid tissue, and choline has often been proposed as a thyroid cancer biomarker . A recently published study showed that the choline-supplemented diet decreased triiodothyronine (T3) and thyroxine (T4) levels in the serum of ducks . Thyroid hormones (TH) are synthesized and released by the thyroid gland and are involved in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…17 A recently published study showed that the choline-supplemented diet decreased triiodothyronine (T3) and thyroxine (T4) levels in the serum of ducks. 18 Thyroid hormones (TH) are synthesized and released by the thyroid gland and are involved in lipid metabolism. Thus, they are consequently highly associated with lipid accumulation.…”
Section: ■ Introductionmentioning
confidence: 99%